P38 MAPK REGULATED XBP1s NUCLEAR TRANSLOCATION AND mRNA STABILITY ARE CRUCIAL FOR MAINTENANCE OF GLUCOSE HOMEOSTASIS IN OBESITY - Sun, Cheng (Nat Med, 2011)
Here we show that p38 mitogen activated protein kinase (p38 MAPK) phosphorylates spliced form of X-Box Binding Protein 1 (XBP1s) on Thr48 and Ser61 residues and greatly enhances nuclear migration of XBP1s. Mutation of Thr48 and Ser61 to alanine dramatically reduces nuclear translocation of XBP1s and activity. We also demonstrate that p38 MAPK activity is markedly reduced in the livers of obese mice and that activation of p38 MAPK by expression of constitutively active MAP Kinase Kinase 6 (MKK6Glu) greatly enhances nuclear translocation of XBP1s, reduces ER stress and establishes euglycemia in the severely obese and diabetic mice. Hence, our results define a crucial role for Thr48 and Ser61 phosphorylations of XBP1s in maintenance of glucose homeostasis in obesity and indicate that p38 MAPK activation in the livers of obese mice may provide a novel therapeutic approach for treatment of type 2 diabetes.